The effect of waves on engine-propeller dynamics and propulsion performance of ships. (1st August 2016) - Taskar, Bhushan; Yum, Kevin Koosup; Steen, Sverre; Pedersen, Eilif
Abstract: This paper investigates the effect of waves on the propulsion system of a ship. In order to study the propulsion in different wave conditions, a procedure for wake estimation in waves has been implemented. A clear drop in the propulsion performance was observed in waves when engine propeller dynamics, wake variation and thrust and torque losses were taken into account. This can explain the drop in vessel performance often experienced in presence of waves in addition to the effect of added resistance. Therefore, performance prediction of ships in rough weather can be improved if the effects of waves on the propulsion system are considered. Specific problems causing drop in performance have also been identified. System response in case of extreme events like propeller emergence has been simulated for analyzing the performance and safety of the propulsion system. The framework of engine-propeller coupling demonstrated in this paper can also be used to analyze different components of propulsion system (e.g. propeller shaft, control system) in higher detail with realistic inputs. This paper is a step towards optimizing the propulsion of ships for realistic operating conditions rather than calm water condition for energy efficient and economic ships. Highlights: Effective method for modeling wake in waves has been demonstrated. Significant changes in the propulsion performance have been observed in waves. Drop in propulsion efficiency due to waves should be taken into account. Wave direction is found to have strong influence on the performance drop.